PENGARUH PENGALAMAN MAGANG DAN SOFT SKILL TERHADAP KESIAPAN KERJA (STUDI KASUS PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS BHAYANGKARA JAKARTA RAYA BEKASI ANGKATAN 2021) - Fitria Chopifah; Hasanuddin Hasanuddin; Jumawan Jumawan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to find out whether Internship Experience and Soft Skills can affect Job Readiness in Students of the Management Study Program, Faculty of Economics and Business, Bhayangkara University, Greater Jakarta. The method of this research is quantitative. The sample used was as many as 45 respondents with the criteria of students of the management study program and who had participated in internships. The data collection technique was in the form of a questionnaire that was compiled in several statements and measured using a likert scale and a sampling technique using purposive sampling. The data analysis technique uses statistical methods with SmartPLS 4.1.8 software. The results of the study show that: 1) Internship Experience has a positive and significant effect on Job Readiness. 2) Soft Skills have a positive and significant effect on Job Readiness.